Exercice 6 :

Développer puis réduire :

A = 3 (x-2) + 5( 3-x)

B= x (3+ x ) - 2( x+5)

C= -2 (x - 7 ) - 2 (x² + 1) + 4 (x² + 1)

D= 2x ( -x + 5) - x² ( 1- x )

E= - 6x (2x² - 3x ) - 3 (x + 4x²) - x( -3 + 4x )

Exercice 7:

Développer puis réduire :

A= 2 (x - 1 ) + 2 (y+2) - 2 (1+z)

B= 3x - (3-3y) + 3 (z+1)

C= (x+y-1) + (x+y+1) - (x+y-z)

D= 2 (x-y) + 3 (y-z) + 4 (z-x) + 3x

E= x (1-y) + y (1-z) + z (1-x) + xy + yz + xz

F= x - [(1-y) - (z+1)]

Merci d'avance! :)

2

Réponses

2013-04-19T17:10:14+02:00

A= 3x-6+15-5x = -2x+9

B= 3x+x²-2x-10 = x+x²-10

C= -2x+14-2x²-2+4x²+4= 2x²-2x+16

D= -2x²+10x-x²+x^3 = x^3-3x²+10x

E=-12x^3+18x²-3x-12x²+3x-4x²= 12x^3+2x²

 

A= 2 (x - 1 ) + 2 (y+2) - 2 (1+z)

  = 2x-2+2y+4-2-2z 

  = 2x+2y-2z

B= 3x - (3-3y) + 3 (z+1)

   = 3x-3+3y+3z+3

   = 3x+3y+3z

C= (x+y-1) + (x+y+1) - (x+y-z)

   = x+y-1+x+y+1-x-y+z

    = x+y+z

D= 2 (x-y) + 3 (y-z) + 4 (z-x) + 3x

   = 2x-2y+3y-3z+4z-4x+3x

   = 5x+y+z

E= x (1-y) + y (1-z) + z (1-x) + xy + yz + xz

   = x-xy+y-yz+z-zx+yz+xy+xz

   = x+y+z

F= x - [(1-y) - (z+1)]

  = x +y+z

2013-04-19T17:11:25+02:00

A= 3 (x-2) + 5( 3-x)

A= 3x -6 + 15 -5x

A= -2x +9

 

B= x (3+ x ) - 2( x+5)

B= 3x + x² -2x -10

B= x² + x -10

 

C=-2 (x - 7 ) - 2 (x² + 1) + 4 (x² + 1)

C= -2x + 14 -2x² -2 + 4x² +4

C= 2x² -2x +16

 

D= 2x ( -x + 5) - x² ( 1- x )

D= -2x -x² -1 x² + x(exposant 3)

D= x(exposant 3) -2x² - 2x

 

E= - 6x (2x² - 3x ) - 3 (x + 4x²) - x( -3 + 4x )

E= -12 x² + 18 x² -3x - 12x² + 3x -4x²

E= -10x²